Mountain law and climate change - Jelev, Viorica (Journal of Economic Development, Environment and People, 2018)
This paper presents 22 indicators used to put into evidence the actual global warming trends. The indicators are the outputs of a detailed research activities performed by scientists from all over the world. These 22 indicators were divided into eight separate categories: atmosphere and climate; glaciers, snow and ice; marine systems; terrestrial ecosystems and biodiversity; water; agriculture; economy; human health. Some specific mountain area aspects are relieved with Mountai Low in Romania.